2017
DOI: 10.5935/medicalexpress.2017.06.03
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of lidocaine patches for pain treatment after total knee arthroplasty

Abstract: BACKGROUND:Effective analgesic therapy in the postoperative period of total knee arthroplasty is essential for good surgical outcomes. The current trend is to use multimodal treatment, in which the use of patches with lidocaine as adjuvant therapy has an increasingly relevant role. OBJECTIVE: To investigate the potential benefits of lidocaine patch association with the basic analgesia regimen for pain relief during the postoperative period of total knee arthroplasty. METHOD: A retrospective cohort study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A recent randomised controlled study conducted on 48 patients for total knee replacement investigated the analgesic effect of LP versus no patch, as an adjuvant to standard analgesics, for 28 postoperative days. The study concluded that LP was effective in reducing pain and decreasing tramadol consumption during the period of the study, and added an analgesic value when used with other multimodal analgesic modalities [23].…”
Section: Discussionmentioning
confidence: 98%
“…A recent randomised controlled study conducted on 48 patients for total knee replacement investigated the analgesic effect of LP versus no patch, as an adjuvant to standard analgesics, for 28 postoperative days. The study concluded that LP was effective in reducing pain and decreasing tramadol consumption during the period of the study, and added an analgesic value when used with other multimodal analgesic modalities [23].…”
Section: Discussionmentioning
confidence: 98%
“… 3 , 15 Sadigursky et al, who performed a trial evaluating the use of T5L patches after TKA, found that the T5L patches decreased narcotic consumption and postoperative pain. 14 Conversely, Khanna et al evaluated 53 patients after TKA and discovered that there was an increase in pain associated with T5L patch use. 10 The mechanism by which lidocaine patches alleviate pain in some musculoskeletal injuries, and not others, is likely secondary to the depth of the injured tissues and the ability of transdermal application to penetrate the soft tissues surrounding traumatized tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial evaluating the use of T5L after arthroplasty found decreased pain at 1 day, 2 days, 3 days, and 2 weeks postop, as well as decreasing opioid medication consumption. 14 In contrast, another study investigating the use of T5L during inpatient rehabilitation after total knee arthroplasty (TKA) found that there was actually an increase in pain associated with T5L patch use. 10 …”
mentioning
confidence: 99%
“…Based on the existing literature on the use of lidocaine patches after noncesarean surgeries, some studies applied the patches directly to the incisions, 38 but other studies demonstrated efficacy when patches were applied around the incision. 36,39,61,62 Thus, the application site may not have been the reason for the lack of efficacy. Second, lidocaine patches may be less effective for laparotomy incisions.…”
Section: Original Researchmentioning
confidence: 99%